How has the Pandemic Affected the Perceived Stress and Coping Behaviours of Nursing Students during Their First Clinical Experience? Impact of The Pandemic on The First Clinical Experience - Genc, Fatma (Advances in Nursing & Midwifery, 2022)
Abstract Introduction: The Covid 19 pandemic has increased the stress and fear of the society. Evaluating the reflections of the pandemic on nursing students' first clinical practices are important in terms of ensuring the adaptation to the practice. The aim of this study is to determine the stress levels and coping behaviours of nursing students during the COVID-19 pandemic. Methods: This study descriptive and correlational. The data were collected from nursing students who were started first clinical practice. This study was carried out in the nursing department of a public university, Turkey. The purposive sampling method was used in this study. The research was carried out with 203 volunteers. The Perceived Stress Scale for Nursing Students (PSSNS), the Coping Behaviours of Stress Scale for Nursing Students (CBSSNS) were used to collect the data and started first experience of clinical practice. Results: The mean age of the students was 20.79±2.29, 79.3% were afraid of having a negative experience. The mean score of PSSNS was 58.23±22.48. The maximum stress experienced by the students was observed in the subscale “stress from taking care of patients” (16.58±6.71). The most frequently used coping behaviour was “Avoidance” (13.39±4.33). Conclusions: It was determined that the nursing students had moderate level of stress during their first clinical practice during the pandemic period, they experienced the most stress while caring for the patient, and they used the avoidance approach the most.